Analisis Standar Perencanaan dan Pengadaan Obat di Apotek Maleo Bintaro - Nurwulan Adi Ismaya; Riris Andriati; Lilis Suryani Butar Butar (Edu Masda Journal, 2020)
Selection and procurement isan important for drugs  in health service. In Maleo Bintaro’s pharmacy, the lateness in fulfilling the needs of medicine because of the industry void, the lateness for the invoice payment and also PBF facilities and infrastructure which is not fast enough cause the inefficient service towards the society. The purpose of these research is to know howdrug’s selection  and procurement in MaleoBintaro pharmacy. This research is descriptive research by retrieving data retrospectively. These are qualitative and quantitative data, also interviews with the related parties. The stage of selection and procurement efficiency is measured by using the indicators which are released by the Ministry of Health (DEPKES) RI in 2002 and Pudjaningsih in 1996. The conclusion of this research is from the 5 indicators which can be measured; 2 indicators have not met the standard yet. First, in the selection stage, the suitability value of the available drugs with DOEN showed 6,78% as the result, and the incomplete letter of the order or the contract showed the result for 12 times. On the other hand, the 3 other indicators which are the frequency of procuring drug items, the lateness in payment from the pharmacy to the specified time, and also the percentage of the number of drugs that are held and planned are effective according to the standard.